Cho ab=1 và a+b≠0. Tính
\(P=\frac{1}{\left(a+b\right)^3}\left(\frac{1}{a^3}+\frac{1}{b^3}\right)+\frac{3}{\left(a+b\right)^4}\left(\frac{1}{a^2}+\frac{1}{b^2}\right)+\frac{6}{\left(a+b\right)^5}\left(\frac{1}{a}+\frac{1}{b}\right)\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{x^3+x^2-4x-4}{x^3+8x^2+17x+10}\)
\(=\frac{x^2\left(x+1\right)-4\left(x+1\right)}{x^3+x^2+7x^2+7x+10x+10}\)
\(=\frac{\left(x^2-4\right)\left(x+1\right)}{\left(x+1\right)\left(x^2+7x+10\right)}\)
\(=\frac{x^2-4}{x^2+7x+10}\)
\(=\frac{x^2-4}{x^2+5x+2x+10}\)
\(=\frac{\left(x-2\right)\left(x+2\right)}{x\left(x+5\right)+2\left(x+5\right)}\)
\(=\frac{x-2}{x+5}\)
Vì \(\left(x^2-x+1\right)^2\ge0\forall x\)
\(\Rightarrow M\ge0\forall x\)
Dấu "=" xảy ra \(\Leftrightarrow x^2-x+1=0\)